Implementasi Pendidikan Karakter dalam Pembelajaran Bahasa Indonesia Kelas VIII SMPN 2 Gunung Omeh Lima Puluh Kota - Zeni, Marta; Gani, Erizal (Lembaga Yasin AlSys, 2023)
The purpose of this research is to describe the character values that have been applied, the supporting and inhibiting factors encountered in the implementation of character education for Indonesian subjects. This type of research is a qualitative research with descriptive method. The data in this study are in the form of opinions, notes on situations and conditions in the field and documents regarding the planning, implementation and assessment of educational character in the process of learning drama texts in class VIII SMP Negeri 2 Gunung Omeh. The data sources for this research are written data sources, interviews, and drama text learning process activities. The data collection techniques for this research are observation, interviews, and documentation. The data analysis techniques of this research are data reduction, data presentation, and conclusions. The results of this study are as follows. First, the teacher implements several character values in learning Indonesian, such as the application of polite and responsible values. Second, the inhibiting factors for the implementation of character education in learning Indonesian in class VIII SMP Negeri 2 Gunung Omeh are the low awareness of students in obeying the rules, student learning motivation is still lacking, student awareness of tasks and responsibilities is still lacking.